2022
DOI: 10.1111/tgis.12980
|View full text |Cite
|
Sign up to set email alerts
|

Flood susceptibility assessment using hybrid machine learning and remote sensing in Quang Tri province, Vietnam

Abstract: Flooding is the most dangerous of all environmental hazards and leads to significant impacts both on the environment and on human life. Environmental protection and water management can be achieved by modeling flood susceptibility, to inform strategy that will reduce flood damage. The aim of this study is to develop novel hybrid models based on a radial basis functions neural network (RBFNN), arithmetic optimization algorithm (AOA), artificial bee colony (ABC), and ant lion optimizer (ALO), to build flood susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 127 publications
(155 reference statements)
1
8
0
Order By: Relevance
“…Such floods are caused by sea level rise; for these events, rainfall is not an important factor. This has been echoed in previous studies (Nguyen, 2022a).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Such floods are caused by sea level rise; for these events, rainfall is not an important factor. This has been echoed in previous studies (Nguyen, 2022a).…”
Section: Discussionsupporting
confidence: 74%
“…Considering the statistical relationships between the conditioning factors and inventory points based on RF, we can see that topographical factors such as elevation and slope are the most influential factors on the probability of flood occurrence in the study area. Several studies have shown that topography influences the hydrological regime that leads to flood (Nguyen, 2022a(Nguyen, , 2022b(Nguyen, , 2022cPham, Vu, et al, 2022). Distance to road, soil, and NDVI ranked third to fifth most important of the 13 factors used.…”
Section: Ta B L Ementioning
confidence: 99%
See 3 more Smart Citations